THE METHOD AND UNITS OF CONCEPTUAL ANALYSIS (Scientific journal of the Fergana State University, 2024)
The article discusses the methods and units of conceptual analysis. The concept has a multidimensional description, in each context the content of its cognitive properties manifests itself in different ways. The concept is evaluated from the point of view of the self-perception of the subject, whose internal state is the carrier. The object of conceptual analysis is a concept, and the concept at the center of the analysis is a way of knowing the semantic meaning of the concept. Conceptual analysis is evaluated as one of the leading methods of studying concepts, and the article examines its analytical manifestations, such as conceptual modeling, gestalt structure and modeling of frame scenarios. Based on conceptual analysis, all knowledge and ideas related to the name denoting a specific concept are restored in the human language landscape. Most of the information collected is made up of metaphorical assessments. We can say that metaphor is a mechanism for understanding abstract concepts that are inaccessible to direct observation. The study of the metaphor mechanism is closely related to the method of conceptual analysis, which, based on deciphering (telling what is) a linguistic metaphor, identifies a “concrete” image interconnected with an abstract concept in a naive picture of the world, and controls its coherence.